Creative writing in post-secondary education: practice, pedagogy, and research - Martin, Lisa Anne (My University, 2025)
A blend of memoir and scholarly review, this book explores the kinds of thinking creative writing, a practical subject, makes possible within secondary education and how it can reimagine higher education in more equitable, diverse, and inclusive directions. Exploring how the subject gives permission to think specifically, locally, from one's own position, and in a necessarily limited way, it considers post-secondary creative writing in its three key aspects-artistic practice, pedagogical practice, and practice-led research. Braiding together disciplinary history, research-informed autobiographical analysis of artistic practice and idea from creativity studies and educational psychology, this is a timely and important discussions likely to spark spirited debate.
Keywords: scholarly review; memoir; post-secondary creative writing